Influence of Substrate Temperature on Structural, Electrical and Optical Properties of ZnO:Al Thin Films - Sudjatmoko Sudjatmoko; Wirjoadi Wirjoadi; B. Siswanto (Atom Indonesia, 2009)
Transparent and conductive aluminium-doped zinc oxide thin films have been prepared by dc magnetron sputtering technique using targets composed of ZnO and aluminium. Polycrystalline ZnO:Al films were deposited onto a heated glass substrate. Surface morphology and crystalline structure as well as optical and electrical properties of the deposited films were found to depend directly on substrate temperature. From optical and electrical analysis it was observed that optical transmittance and conductivity of the ZnO:Al transparent conductive oxide films increased when the deposition temperature was raised from 200 to 400 oC. Films grown on substrates heated at 300 oC showed a high conductivity value of 0.2 x 102 Ω-1cm-1 and a visible transmission of about 80%. The growth of ZnO:Al thin films on the surface of glass substrate at temperatures of 300 oC and aluminium doping levels of 0.9 at.% were the best to attain ZnO:Al films with optical and structural qualities as required for solar cell applications, as a window material in antireflection coatings or optical filters.Received: 17 March 2009; Revised: 22 November 2009 ; Accepted: 23 November 2009